PENGARUH TEKNIK MARMET TERHADAP KELANCARAN PRODUKSI ASI PADA IBU MENYUSUI DI PUSKESMAS SENAPELAN - Ade Febriana; Elvira Elvira (Collaborative Medical Journal, 2024)
Lactation is the entire breastfeeding process starting from the production of breast milk (ASI) to the process of the baby sucking and swallowing breast milk. Mother's milk is the natural first food for babies. Low production and ejection of breast milk (ASI) in the first days causes many mothers to experience ineffective breastfeeding. The lack of production of breast milk is caused by a lack of stimulation of the hormone prolactin. The marmet technique is a combination of expressing and massaging the breasts of postpartum mothers which can stimulate hormones in the breastfeeding process. This study aims to determine the effect of the marmet technique on breastfeeding mothers. This research is quantitative research with a quasi-experimental study approach (Quasi Experiment) using a Pre and post Test without Control design. This type of research is research without comparisons or groups that must be controlled. The target population in this study was all 15 breastfeeding mothers at the Community Health Center. The research was carried out in May-July 2023. The research results showed that 5 mothers (33.34%) had smooth breast milk production before being given the marmet technique and 11 people (73.34%) had fluency after being given the marmet massage. The statistical test results obtained a P-value of 0.011 (<0.05) where there was a significant difference in breast milk production before and after the marmet technique. Giving the marmet technique treatment causes breast milk to flow more smoothly. More respondents felt that the flow of breast milk was faster when breastfeeding